Natural polymers for vaginal mucoadhesive delivery of vinegar, using design of experiment methods - Parvinroo, Shirin; Eslami, Maede; Ebrahimi-Najafabadi, Heshmatollah; Hesari, Zahra (Vojnosanitetski pregled, 2022)
Background/Aim. Vinegar is one of the main international traditional nutraceuticals, and it has been used as a vaginal health protectant due to vagina pH balance maintenance and antimicrobial properties. Since the main form of vinegar is liquid, it is difficult to apply vaginally due to its short retention. The aim of this study was to design a vaginal mucoadhesive gel made of vinegar. Methods. Xanthan gum and tragacanth were utilized as natural gel-forming polymers. The effects of xanthan gum and tragacanth on mucoadhesion strength and drug release of the gel formulations were optimized using a 3 level (32) factorial design. Several physico-chemical properties of the gel formulations, including gel viscosity, lubricity, scanning electron microscopy (SEM) images of hydrogel chains, and chain release kinetic, were also investigated. Results. It was found that tragacanth possessed a statistically significant effect on release rate control (p-value = 0.0027), while both tragacanth and xanthan gum had a significant effect (p-value = 0.0001 and 0.0017, respectively) on mucoadhesion property. Formulation F7 with 5% xanthan gum and 1% tragacanth (mucoadhesion = 0.4632 N and release rate = 88.8% in 6 hours) considered as the optimum formulation with some modifications. Conclusion. Xanthan gum and tragacanth can be considered as appropriate natural polymers for vaginal drug delivery.